Racial Disparities in the Arteriovenous Fistula Care Continuum in Hemodialysis Patients - Qian, Joyce (Clin J Am Soc Nephrol, 2020)
BACKGROUND AND OBJECTIVES: Arteriovenous fistulas are the optimal vascular access type for patients on hemodialysis. However, arteriovenous fistulas are used less frequently in Black than in White individuals. The arteriovenous fistula care continuum comprises a series of sequential steps. A better understanding is needed of where disparities exist along the continuum in order to mitigate racial differences in arteriovenous fistula use. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: Using Medicare claims data from the United States Renal Data System, longitudinal analyses of patients ≥67 years initiating hemodialysis with a central venous catheter between July 1, 2010 and June 30, 2012 were performed. Three patient cohorts were identified: patients initiating hemodialysis with a catheter (n=41,814), patients with arteriovenous fistula placement within 6 months of dialysis initiation (n=14,077), and patients whose arteriovenous fistulas were successfully used within 6 months of placement (n=7068). Three arteriovenous fistula processes of care outcomes were compared between Blacks and Whites: (1) arteriovenous fistula creation, (2) successful arteriovenous fistula use, and (3) primary arteriovenous fistula patency after successful use. RESULTS: An arteriovenous fistula was placed within 6 months of dialysis initiation in 37% of patients initiating dialysis with a catheter. Among the patients with arteriovenous fistula placement, the arteriovenous fistula was successfully used for dialysis within 6 months in 48% of patients. Among patients with successful arteriovenous fistula use, 21% maintained primary arteriovenous fistula patency at 3 years. After adjusting for competing risks, Black patients on hemodialysis were 10% less likely to undergo arteriovenous fistula placement (adjusted subdistribution hazard ratio, 0.90; 95% confidence interval, 0.87 to 0.94); 12% less likely to have successful arteriovenous fistula use after placement (adjusted subdistribution hazard ratio, 0.88; 95% confidence interval, 0.83 to 0.93); and 22% less likely to maintain primary arteriovenous fistula patency after successful use (subdistribution hazard ratio, 0.78; 95% confidence interval, 0.74 to 0.84). CONCLUSIONS: Lower arteriovenous fistula use among Blacks older than 67 years of age treated with hemodialysis was attributable to each step along the continuum of arteriovenous fistula processes of care.